Carbonised plant remains (Scottish Historical and Archaeological Internet Reports, 2011)
During the earlier phases of occupation the surrounding woodlands wee probably still relatively undisturbed providing a range of typical lowland woodland tree species for fuel and construction. Hazel nut fragments in some pits may indicate a Mesolithic or early Neolithic date. Evidence for Neolithic agriculture was found in the form of carbonised emmer and bread wheat together with naked barley. Charcoal production was taking place and may be related to industrial activity of some kind.